SEDIMENTOLOGI FORMASI WORAWARI PALEOGEN DI PEGUNUNGAN SERAYU UTARA - Syaiful Bachri; Hermes Panggabean (Jurnal Geologi dan Sumberdaya Mineral, 2010)
The Worawari Formation is a new name proposed in this paper, comprising Paleogene deep marine sediments and cropped out in the Banjarnegara and the surrounding area. The formation comprises turbidite deposits in the lower part, and upwards it develops into olistostrome deposits consisting of claystone matrix and boulders having tens meters in size, and comprising polimictic conglomerate, sandstone, and numulitic limestone. In the Gebyugan River, a small tributary of the Worawari River, the lower part of the Worawari Formation consists of siltstone and very fine to fine sandstone and claystone. These rocks contain abundantly fossils of radiolaria, bathysiphon, fish teeth and bentonic fossils suggesting a deep marine environmrent. Meanwhile, an exposure of alternating claystone and sandstone was found in Kali Tengah River, containing trace fossils of paleodicton type indicating a deep marine environment. Boulders of sandstone and polimictic conglomerate are found in Kali Tengah River and Kali Tulis River, while numulitic boulders are exposed in the upstream area of the Worawari River. The claystone containing boulders of various types of rock is interpreted to be olistostrome deposits.Keywords: Worawari Formation, Paleogene sediments, turbidites, olistostrome, deep marine, North Serayu Mountain